Methodological guide for participatory collection of gender indicators in agriculture used by SwissContact in the Rural Opportunities Project in Golfo de Fonseca, Honduras - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The guide was used to collect qualitative data on perceptions and household and community dynamics surrounding women’s empowerment from producers and processors of cashew, fruits and dairy products in the Rural Opportunities Project implemented by SwissContact in the Gulf of Fonseca, Honduras.